2010
DOI: 10.1093/occmed/kqq127
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health of municipal solid waste workers

Abstract: The results of this cross-sectional study indicate a higher prevalence of respiratory symptoms and a greater decrease in lung function in MSWWs. A number of limitations such as the relatively small size of population and the 'healthy worker' effect should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 18 publications
7
57
2
5
Order By: Relevance
“…These workers abuse substances like tobacco 2 (10%) and ghutka 18 (90%). The results of the study are in accordance with Athanasiou et al, 2010;Ajay et al, 2014, Lavoie and Dunkerley 2002, Nayera et al, 2015, Sabde and Zodpe 2008, Shrinivasan et al, 2012, Stambuli 2012, Wassim et al, 2013 Comparative analysis of PEFR values between municipal solid waste collecting workers and control group is presented in Table 6. Minimum, maximum and average PEFR values of male and female workers for exposure period of 10-20 years, 21-24 years and >25 years shows that average PEFR values in female decreases as the exposure period increases.…”
Section: Results Of the Study Are Presented In Tables 2-6 And Figuressupporting
confidence: 85%
See 1 more Smart Citation
“…These workers abuse substances like tobacco 2 (10%) and ghutka 18 (90%). The results of the study are in accordance with Athanasiou et al, 2010;Ajay et al, 2014, Lavoie and Dunkerley 2002, Nayera et al, 2015, Sabde and Zodpe 2008, Shrinivasan et al, 2012, Stambuli 2012, Wassim et al, 2013 Comparative analysis of PEFR values between municipal solid waste collecting workers and control group is presented in Table 6. Minimum, maximum and average PEFR values of male and female workers for exposure period of 10-20 years, 21-24 years and >25 years shows that average PEFR values in female decreases as the exposure period increases.…”
Section: Results Of the Study Are Presented In Tables 2-6 And Figuressupporting
confidence: 85%
“…According to Athanasiou et al, (2010), prevalence of all respiratory symptoms were higher in municipal solid waste collecting workers headache (36%), sore throat (17%) and rhinitis (33%), than in control group. Ajay et al, 2014 reported that Peak Expiratory Flow…”
Section: Results Of the Study Are Presented In Tables 2-6 And Figuresmentioning
confidence: 89%
“…Few studies in the literature have investigated pathogenic pathways of respiratory impairment: beta-(1-3)-glucans and similar volatile compounds (NO 2 , SO 2 , CO, etc.) [74] are thought to be able to release several types of cytokines from neutrophils and monocytes, such as IL-6, IL-8 and TNF-alpha, and to promote epithelial inflammation in upper and lower airways, ultimately resulting in obstructive diseases [75,76]. However, other studies did not confirm these data, and further investigations are required [77].…”
Section: Discussionmentioning
confidence: 99%
“…Otras publicaciones encontraron datos de exposición a riesgos biológicos, químicos, físicos, ergonómicos, aspectos psicosociales (10); en otras se buscaron condiciones de salud, afecciones respiratorias y ergonómicas (11)(12)(13).…”
Section: Introductionunclassified